The societal impact of treatment with natalizumab of relapsing–remitting multiple sclerosis in Italian clinical practice: The Tysabri® PharmacoEconomics (TyPE) Study. (June 2019) - Polistena, B; Spandonaro, F; Capra, R; Fantaccini, S; Santoni, L; Zimatore, GB; Gasperini, C
Multiple sclerosis progressively impairs patients' ability to independently perform activities of daily living, reduces working capacity, and negatively affects social interactions and relationships, imposing a cost for the society. The aim of this study was to explore the impact on society of treatment of multiple sclerosis with natalizumab in Italian clinical practice. A prospective, observational study was conducted in 24 specialized centers throughout Italy. Direct and indirect costs, as well as the health-related quality of life of patients undergoing treatments, were estimated, while societal impacts were determined using a cost-utility approach. Non-medical direct and indirect costs accounted for 55.7% of the total cost prior to treatment and up to 47.5% after treatment with natalizumab. From the social perspective, greater medical direct costs for second-line drug treatment are nearly offset by savings on non-medical direct costs and by greater productivity, resulting in a +0.5% incremental cost. Assuming a societal perspective, the first year of treatment with natalizumab in real-world clinical practice results in an incremental cost of €2814.8/quality-adjusted life year gained. Multiple sclerosis imposes a considerable burden on patients, their families, and caregivers, stressing the importance of considering the societal perspective in the appraisal process. Treatment with natalizumab shows a noteworthy benefit in social terms.